If f(x) = 3x - 2 and g(x) = x2 +1, find (f +9)(x).
![If fx 3x 2 and gx x2 1 find f 9x class=](https://us-static.z-dn.net/files/d7b/9ad7728c14d52b17a346b80714d9d56c.jpg)
Answer:
A. x² + 3x - 1
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
Algebra I
Step-by-step explanation:
Step 1: Define
Identify
f(x) = 3x - 2
g(x) = x² + 1
(f + g)(x) is f(x) + g(x)
Step 2: Find
Answer:
D. x² + 3x + 1
Step-by-step explanation:
Given :- f ( x ) = 3x - 2 ɑnd g( x) = x² + 1
Find :- ( f + g ) ( x )
Solution :-
( f + g ) ( x ) = ( ( 3x - 2 ) + ( x² + 1))
( f + g ) ( x ) = ( 3 x - 2 + x² + 1 )
( f + g ) ( x ) = ( x² + 3x - 1 )